LANGUAGE AS THE MIRROR OF A NATION: THE STRATEGIC ROLE OF THE STATE LANGUAGE IN SOCIAL DEVELOPMENT - Dilshod Zarif o'g'li Kushanov; Halim Zarif o'g'li Xurramov; Zaripova Aziza Shaxobiddinovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article investigates the role of language not only as a tool for communication but as a symbol of state independence, the foundation of national identity, and a driver of social progress. The article analyzes the legal status of the Uzbek language, its role in public administration, education, science, and digital technologies. Furthermore, it justifies the strategic importance of preserving and developing the state language in the context of globalization.